2017
DOI: 10.1111/jocd.12356
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of microneedling and autologous platelet‐rich plasma in the treatment of atrophic scars: A randomized study

Abstract: Although a single treatment may give good results, combination between skin needling and platelet-rich plasma is more effective, safe with less number of sessions in all types of atrophic scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 35 publications
4
66
0
11
Order By: Relevance
“…These studies report 57 participants with Fitzpatrick type 5 skin, 138 with type 4, 78 with type 3 and 34 with type 2. The differences between the groups were not significant, with the exception of Ibrahim ZA and co‐authors having a significantly greater amount of skin type 4 in his control group (OR 0.27; CI: 0.08‐0.88) …”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…These studies report 57 participants with Fitzpatrick type 5 skin, 138 with type 4, 78 with type 3 and 34 with type 2. The differences between the groups were not significant, with the exception of Ibrahim ZA and co‐authors having a significantly greater amount of skin type 4 in his control group (OR 0.27; CI: 0.08‐0.88) …”
Section: Resultsmentioning
confidence: 80%
“…One study (56 participants) reported the degree of pain after either combined or monotherapy. Ibrahim ZA and co‐authors found no differences in the degree of pain experienced between microneedling with PRP and microneedling alone (MD −0.10, [−0.50, 0.30]; P = .64) …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The severity of acne scars has reduced after treatment with dermapen in most of the patients of group I, two patients had no improvement with dermapen, and this might be due to long duration of scar. In parallel with this study, Ibrahim et al used dermapen for treatment of atrophic scars. They conducted a study in which all patients in the dermapen group showed improvement; better response was observed in non‐acne scars than acne scars, although the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 77%
“…Group I: We primed the patients with topical vitamin A and C formulations twice a day for 2 weeks to maximize dermal collagen formation. We adapted the technique described by Ibrahim et al Microneedling treatment was performed with dermapen (Bomtech Electronics, Seoul, Seocho‐Gu, Korea (34, Hyoryeong‐ro 49‐gil, Seocho‐gu, Seoul, JX‐120DR). Thick layer of local anesthetic EMLA cream (eutectic mixture of lidocaine and prilocaine), APP Pharmaceuticals, Fresenius Kabi, San Francisco, IL, USA) was applied to the face for approximately 45‐60 minutes before the procedure.…”
Section: Methodsmentioning
confidence: 99%